TEKNOLOGI TEPAT GUNA (TTG) DI WILAYAH TERTINGGAL PADA MASYARAKAT SUKU DAYAK ASLI PEDALAMAN KALIMANTAN BARAT - Eko Sarwono; Linda Suwarni; Selviana Selviana (Universitas Muhammadiyah Pontianak, 2016)
Kubu Raya is a new district, the expansion of Pontianak regency in which still needs restructuring, and organizational, and administrative territory revamping. This condition will affect the social environment, the economy and the health of local communities. One of district in Kubu Raya Regency, Sungai Ambawang district, contained several underdeveloped villages. The majority people there are indigenous Dayak. Their customs are dominantly affected their social system . Human Development Index (HDI) of Kubu Raya in 2012 amounted to 69.42, where the rate is still below of the IPM Kalbar is 70.31 and Indonesia is 73.29. Community service activities is aimed at improving the productivity of fisheries communities in civilizing the utilization of river water through the application of appropriate technology (TTG) to improve the welfare of the communities in the disadvantaged areas. The method implemented was a partnership with the government of village, district, and related agencies, as well as participatory methods that involve communities actively in the implementation of the application of appropriate technology (TTG), so that people can produce and be able to apply these technologies in daily life in the disadvantaged areas to empower indigenous Dayak communities inland through the Appropriate Technology (TTG). The implementation of Appropriate Technology was the result of this activity. In the field of health technology built filtering water, whereas in the field of fisheries technology development and training pool tarp fish feed production, all of which was made as a pilot which aimed that the application of technology is so easily imitated and implemented by the community. Transfer of knowledge and skills to the community has been implemented in various fields, and it needs optimal development resulting in the improvement of health, economic and social welfare in indigenous Dayak inland region. Therefore, the cooperation among the governments of villages, districts and related agencies and universities need to be done so the promotion and development Appropriate Technology, especially in the district of Kubu Raya Ambawang be sustained to achieve a healthy and prosperous society.Keywords: Appropriate Technology, filtering water, vegetable gardening, SRI, selendang polan, backward Areas.